ICRISAT Showcases Scalable Regenerative Landscapes for Water Security - Anantha, K.H.; Venkata Radha, A.; Reddy, Nagarjuna, N.; Garg, Kaushal K.; Singh, Ramesh (International Crops Research Institute for the Semi-Arid Tropics, 2025)
A team of scientists from ICRISAT (Drs. Anantha KH, Venkata Radha A, and Nagarjuna N Reddy) participated in the 35th edition of World Water Week, where the global community convened under the theme “Water for Climate Action.” Supported by the CGIAR Multifunctional Landscapes (MFL) Science Program, the team utilized this global platform to foster engagement and cross-regional learning on sustainable ecosystem management. The CGIAR MFL Science Program is a holistic research initiative that envisions vibrant, diverse, and resilient landscapes managed to simultaneously deliver sustainable eco-agrifood systems, healthy diets, and climate resilience, all while staying within planetary boundaries.